Peningkatan Kemampuan Mengenal Angka melalui Media Sticky Note Counting Flower pada Anak Usia 4-5 Tahun - Puji Anik; Mochammad Maulana Trianggono; Rizki Sevi Triana; Firman Ashadi (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
Number recognition ability are an important part of early childhood cognitive development. At this stage children begin to understand the concept of numbers and numerals, and are able to recognise and name basic numbers. This study aims to improve the ability to recognise numbers concretely, strengthen basic numerical skills and increase their interest in learning mathematics from an early age. This research was conducted through classroom action research (PTK). The research subjects consisted of 12 group A students aged 4-5 years. The classroom action research conducted adopted the Kurt Lewin model which consists of planning, implementation, observation, and reflection. The results showed an increase in students' ability to recognise numbers. The increase in the ability to recognise numbers can be seen in the pre-cycle the number of children who developed very well / optimally or 25% of students, increased in cycle I to 50% of the number of students who developed very well / optimally, and in cycle II increased to 75% of students developing very well / optimally. The Sticky Note Counting Flower Media that is applied is able to provide opportunities for students to learn more deeply about basic numbers, making it easier for students to remember and reinterpret. Therefore, it can be concluded that Sticky Note Counting Flower Media can optimally improve the ability to recognise numbers in children aged 4-5 years.